AN INVESTIGATION OF THE EFFECT OF THE ISO 9001 QUALITY MANAGEMENT SYSTEM ON SMALL AND MEDIUM ENTERPRISES IN GAUTENG, SOUTH AFRICA - Magodi, Aluwani Yvonne; Daniyan, Ilesmni Afolabi; Mpofu, Khumbulani (The South African Journal of Industrial Engineering, 2022)
The implementation of quality management systems (QMS) is central to the performance of small and medium enterprises (SMEs). At present, there is a lack of information about the level of adoption and implementation of QMS by SMEs in Gauteng Province, even though that province has the highest number of SMEs in South Africa (SA). This study therefore aims to investigate the effect of the ISO 9001 QMS on SMEs in Gauteng. Quantitative research was conducted, and an online survey was used to collect data. An inferential statistical data analysis involving the Statistical Package for the Social Sciences (SPSS) software was used to analyse the collected data. The chi-square and Fischer’s exact tests were applied to validate the statistical significance of four hypotheses. The inferential analysis showed that there is a relationship between ISO 9001 implementation and SMEs’ sustainability, as well as a direct relationship between the implementation of ISO 9001 and the performance, growth, and life span of SMEs in Gauteng Province. In addition, the results indicated that 64 per cent of the surveyed SMEs are aware ISO 9001, while 36 per cent of SMEs were not aware of QMS. The survey indicated that SMEs face several challenges, such as the ineffective implementation of QMS, poor funding, a low level of human capacity development, a lack of adequate resources, poor working environment, and poor work organisation, a lack of necessary materials, and the use of inappropriate work methods. It is envisaged that, if a culture of QMS were to be adopted and implemented by SMEs, there would probably be an improvement in operational efficiency, leading to improved customer satisfaction and increased turnover and profitability.